Penerapan Konseling Kelompok dengan Teknik Self Management untuk Mengurangi Kecanduan Media Sosial Siswa Kelas VIII SMP Negeri 1 Bontang - Ulkia Ilmi; Yashinta Sari Pratiwi; Dwi Sona (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
This study aims to determine the effectiveness of group counseling with self-management techniques in reducing social media addiction in students of SMP Negeri 1 Bontang. The experimental design used in this study was a one-group pretest-posttest. The treatment was carried out in accordance with group counseling with self-management techniques which consists of four stages, namely self-monitoring, self-commitment (self-contracting), self-evaluation, and reinforcement, elimination, or punishment (self-reward). The study population was 34 students, with a sample of 6 students who had a high level of social media addiction. The sampling technique used was purposive sampling. Indicators used to measure the level of social media addiction of students included virtual tolerance, virtual communication, virtual problems, and virtual information. The results showed that the average score of social media addiction decreased from 107 (high category) at the pretest to 46.3 (low category) at the posttest. All research subjects experienced a consistent decrease in scores after participating in the counseling series. The results of the paired sample t-test confirmed these findings with a significance value of 0.001 (p < 0.05), indicating a statistically significant difference between social media addiction scores before and after treatment. Overall, it can be concluded that group counseling with self-management techniques can be applied to reduce students' social media addiction.